Article RETRACTED due to manipulation by the authors Analyzing the role of motor skill training on critical reading ability in elementary school students - Octavian Muning Sayekti; Anwar Efendi; Sujarwo Sujarwo; Hendra Setyawan; Hari Sunaryo; Sahabuddin Sahabuddin; Sabariah Sabariah; Rufi’i Rufi’i; Harmanto Harmanto; Baskoro Nugroho Putro; Susanto Susanto; Zulbahri Zulbahri; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study used the systematic literature review to explore the role of motor skills training on critical reading skills in elementary school students. Data were obtained from articles searched through Google Scholar. The search focused on those published in Scopus-indexed journals between 2019 and 2024. As a result, 17,400 articles were found. These articles were screened again in several stages. Some criteria were applied to determine whether the articles should be included or excluded. In addition, the study employed specific keywords, such as "Role and Practice AND Motor Skills AND Critical Reading Ability AND Elementary School Students". These stages then generated 20 articles that fit the theme and met the inclusion requirements. During the article selection, this study followed the PRISMA guidelines. The key findings of this study confirmed that the development of gross and fine motor skills has a significant role in supporting the development of cognitive and academic abilities, especially in improving critical reading skills in elementary school students. This study revealed the positive relationship between motor skills and academic achievement, supported by stimulating physical environments and play-based learning approaches. This finding emphasizes the importance of integrating physical activity into the primary education curriculum. In addition, the findings highlighted the roles of support from various parties, including teachers, parents, and communities. Such supports are needed to ensure a conducive environment for developing students' motor and cognitive skills. Despite these findings, challenges such as lack of sports facilities, gender differences, and an unbalanced curriculum must be overcome to achieve optimal results. These findings imply the need for a holistic approach to education, emphasizing not only focuses on academics but also motor development to support critical reading skills for students' future academic success.